Biology's Best Friend: Bridging Disciplinary Gaps to Advance Canine Science. (13th May 2021) - Bryce, Caleb M; Davis, Michael S; Gompper, Matthew E; Hurt, Aimee; Koster, Jeremy M; Larson, Greger; Ostrander, Elaine A; Udell, Monique A R; Urfer, Silvan; Wirsing, Aaron J; Jimenez, Ana G
Synopsis: The rich history and global abundance of domestic dogs ( Canis familiaris ) present a unique opportunity and an ideal model for interdisciplinary research. Canine evolutionary history demonstrates unprecedented changes across all levels of biological organization. These include diversification from highly social, pack-dwelling wild carnivores (extant gray wolves, C. lupus ), to increased dependence on humans (domestication), to modern in-home colonization featuring close physical proximity to humans (interspecies bonding). The young, emerging field of "canine science" comprises numerous biological disciplines including evolution, genetics, cognition, behavior, physiology, comparative medicine, and ecology, drawing on studies of both natural and experimental systems and scaling across all levels of biological organization, from genomes to ecosystems. However, limited connections bridge the diverse fields associated with canine science, although in every branch it is recognized that this species is one of the most phenotypically variable mammals. However, there has been growing interest in integrating the insights from genomic evolution with those from ecophysiology and ecology, thus facilitating a more biologically comprehensive perspective of dogs. In particular, integrative, mechanistic, and/or ecological studies have been generally underrepresented. To address these emerging interests, we have collected the most compelling questions in the field of canine biology and present avenues of current and future research. This article serves to both orient the reader to this special issue, as well as offer a forward-looking perspective from diverse biological sub-disciplines to highlight current and future goals in canine research.